Effectiveness and Efficiency of Use "Property Management System (PMS)" in The Front Office Division of Hotel “X” and Hotel “Y” in Center Jakarta - Yanti Nirmala (Eduvest - Journal of Universal Studies, 2021)
The hotel is closely related to the front office division, and in carrying out its duties serving guests. This department requires a computer system capable of meeting customer needs. There are several computer systems available at this time, however the author limits them to only 2 (two) PMS systems which will be discussed in this paper at the “X” and “Y” hotels in Central Jakarta. This study uses a quantitative approach. The research method used by the author is to use a Likret scale. The source of the data obtained by the author is data from the front office divisions at the "X" hotel and the "Y" hotel in Central Jakarta. The data analysis technique that the writer uses in this paper is the Multiple Linear Regression Model. After doing research, the authors found that the front office division was effective because it used the PMS. Its effectiveness has a significant effect on the use of PMS with a contribution of 26.2%. The front office division is also efficient because it uses PMS. Its efficiency has a significant effect on the use of PMS with a contribution of 63.5%. Effectiveness (X1) and Efficiency (X2) together have a significant effect with a strong category on the use of PMS (Y) with a contribution of 67.7%, the remaining 32.3% is influenced by other factors not included in in this research.